Perinatal continuity of care for mothers with depressive symptoms: perspectives of mothers and clinicians - Barr, Karlen R.; Nguyen, Trisha A.; Pickup, Wendy; Cibralic, Sara; Mendoza Diaz, Antonio; Barnett, Bryanne; Eapen, Valsamma (Frontiers in Psychiatry, 2024)
Background: Mothers with mild to moderate depression in pregnancy are at risk of developing postpartum depression. Midwife-led continuity of care may support maternal mental health throughout the perinatal period. Research is needed to better understand how continuity of care may support mothers experiencing depression in pregnancy. This study aimed to investigate the perspectives of mothers with mild to moderate depression and clinicians regarding continuity of care in the perinatal period.Method: Fourteen mothers and clinicians participated in individual interviews or a focus group.Analysis was conducted using inductive reflexive thematic analysis with a constructivist orientation.Results: From the perspectives of mothers and clinicians, continuity of care during the antenatal period benefitted mothers' mental health by providing connection and rapport, information about pregnancy and referral options, and reassurance about whether pregnancy symptoms were normal. The experience of seeing multiple clinicians was noted by mothers to increase distress while participants discussed the value of extending continuity of care into the postpartum period, including having someone familiar checking in on them. The importance of having a second opinion and not always relying on a single provider during pregnancy was highlighted by some mothers and clinicians. Mothers also described how multiple modes of communication with a midwife can be helpful, including the ease and accessibility of text or email.Mothers and clinicians perceived benefits of continuity of care for maternal mental health. Offering midwife-led continuity of care to mothers with mild to moderate depression during the perinatal period is recommended.